MRI of Adenomyosis: Where Are We Today?. Issue 1 (February 2023) - Zhang, Michelle; Bazot, Marc; Tsatoumas, Maria; Munro, Malcolm G.; Reinhold, Caroline
Purpose of Review: The purpose of this review is to (i) summarize the current literature regarding the role of magnetic resonance imaging (MRI) in diagnosing adenomyosis, (ii) examine how to integrate MRI phenotypes with clinical symptomatology and histological findings, (iii) review recent advances including proposed MRI classifications, (iv) discuss challenges and pitfalls of diagnosing adenomyosis, and (v) outline the future role of MRI in promoting a better understanding of the pathogenesis, diagnosis, and treatment options for patients with uterine adenomyosis.Recent Findings: Recent advances and the widespread use of MRI have provided new insights into adenomyosis and the range of imaging phenotypes encountered in this disorder.Summary: Direct and indirect MRI features allow for accurate non-invasive diagnosis of adenomyosis. Adenomyosis is a complex and poorly understood disorder with variable MRI phenotypes that may be correlated with different pathogeneses, clinical presentations, and patient outcomes. MRI is useful for the assessment of the extent of findings, to evaluate for concomitant gynecological conditions, and potentially can help with the selection and implementation of therapeutic options. Nevertheless, important gaps in knowledge remain. This is in part due to the lack of standardized criteria for reporting resulting in heterogeneous and conflicting data in the literature. Thus, there is an urgent need for a unified MRI reporting system incorporating standardized terminology for diagnosing adenomyosis and defining the various phenotypes.